2011
DOI: 10.1016/j.cub.2011.10.039
|View full text |Cite
|
Sign up to set email alerts
|

The rubber hand illusion increases histamine reactivity in the real arm

Abstract: Brower and others have argued that the evolution of mankind might have come to a halt without optimistic illusions. With the emergence of conscious foresight (the ability to imagine one's future) came the devastating understanding that old age, sickness, decline of mental power, and oblivion await. Varki and Brower reason that this awareness on its own would have interfered with our daily function, bringing the activities needed for survival to a stop. However, if conscious foresight evolved alongside optimist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 11 publications
8
111
0
1
Order By: Relevance
“…Skin conductance response increased in the phases leading up to perceptual embodiment, consistent with other investigations and reflecting general physiological arousal [12,23,24]. The phases leading up to perceptual embodiment have also been associated with various physiological correlates including proprioceptive drift [25], local skin cooling [26,27], local histamine reactivity [28] and alterations of neural activity in the brain [29], although confounding variables reduce the reliability of these correlates as indicators of the subjective experience of the sense of self and body ownership [30,31].…”
Section: Discussionsupporting
confidence: 64%
“…Skin conductance response increased in the phases leading up to perceptual embodiment, consistent with other investigations and reflecting general physiological arousal [12,23,24]. The phases leading up to perceptual embodiment have also been associated with various physiological correlates including proprioceptive drift [25], local skin cooling [26,27], local histamine reactivity [28] and alterations of neural activity in the brain [29], although confounding variables reduce the reliability of these correlates as indicators of the subjective experience of the sense of self and body ownership [30,31].…”
Section: Discussionsupporting
confidence: 64%
“…The present data are thus compatible with previous accounts of a weak link between proprioceptive drift and selfattribution (i.e., Makin et al, 2008), suggesting that these measures concern related but distinct mechanisms. The changes in body ownership induced by the RHI have been quantified by a wide range of implicit measurements, including skin conductance (Armel & Ramachandran, 2003), cooling of skin temperature (Moseley et al, 2008), visuotactile perception (Aspell, Lenggenhager, & Blanke, 2009;Zopf, Savage, & Williams, 2010), changes in heartbeat frequency (Tsakiris, Tajadura-Jimenez, & Costantini, 2011), and histamine reactivity (Barnsley et al, 2011). Based on our results showing changes in MR performance under conditions that also induced changes in body ownership, we propose that (1) MR and the RHI share sensory-motor and multisensory mechanisms and (2) the speed of MR-and in particular, the magnitude of the interaction between the direction of MR and the stimulus view-should be added to the list of behavioral measures of the RHI.…”
Section: Subjective Versus Behavioral Measurements Of the Rhimentioning
confidence: 99%
“…It has been suggested that a threat to the rubber hand can cause a similar level of activity in the brain areas associated with anxiety as when the person's real hand is threatened (Ehrsson, Wiech, Weiskopf, Dolan, & Passingham, 2007). The physiological signals that are usually recorded are skin conductance (Armel & Ramachandran, 2003;Honma, Koyama, & Osada, 2009;Petkova & Ehrsson, 2008;Petkova et al, 2011;Yuan & Steed, 2010), electrocardiogram (ECG) (Maselli & Slater, 2013;Slater et al, 2010), changes in temperature (Hohwy & Paton, 2010;Moseley et al, 2008), temperature sensitivity threshold (Llobera, Sanchez-Vives, & Slater, 2013), and histamine reactivity (Barnsley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%